Dialogue among civilizations : (Unesco, 2006)
Dialogue Among Civilizations explores the social, cultural, and philosophical underpinnings of "civilizational dialogue" by asking questions like these: What is the meaning of such dialogue? What are its preconditions? Are there different trajectories for different civilizations? Is there also a dialogue between past and future involving remembrance?